1996
DOI: 10.1210/jcem.81.5.8626850
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to steroidogenic enzymes in autoimmune polyglandular syndrome, Addison's disease, and premature ovarian failure.

Abstract: Autoantibodies to steroidogenic enzymes, steroid 17 alpha-hydroxylase (17 alpha-OH), cytochrome P450 side-chain cleavage enzyme (P450scc), and steroid 21-hydroxylase (21-OH), were measured using specific and sensitive immunoprecipitation assays (IPAs) in patients with various forms of autoimmune adrenal disease. Autoantibodies to 17 alpha-OH were detected in 6 of 11 (55%) patients with autoimmune polyglandular syndrome (APS) type I, 8 of 24 (33%) patients with APS type II, 11 of 56 (20%) patients with adrenal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
85
1
6

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 14 publications
7
85
1
6
Order By: Relevance
“…There were, however, some discrepancies in the different studies regarding the reactivity and the prevalence of autoantibodies to 17a-OH and P450scc in patients with PGAD type 1, type 2 or isolated AAD (52,53,55,57,58,61). The reasons for these differences could be related, at least in part, to the sources of autoantigens used to detect autoantibodies (62).…”
Section: Adrenal Autoantigensmentioning
confidence: 99%
See 2 more Smart Citations
“…There were, however, some discrepancies in the different studies regarding the reactivity and the prevalence of autoantibodies to 17a-OH and P450scc in patients with PGAD type 1, type 2 or isolated AAD (52,53,55,57,58,61). The reasons for these differences could be related, at least in part, to the sources of autoantigens used to detect autoantibodies (62).…”
Section: Adrenal Autoantigensmentioning
confidence: 99%
“…Reports on identification of 21-OH as a major adrenal autoantigen were confirmed by studies in several laboratories using different methods, including Western blotting or immunoprecipitation analyses based on native or recombinant 21-OH expressed in bacteria, yeast, mammalian cells or in vitro transcription/translation system (54-57). In addition, recent studies have shown that 21-OH is the major adrenal autoantigen in AAD irrespective of whether the disease presents as isolated AAD or PGAD type 1 or type 2 or in ACA-positive patients without overt AAD (58,59). Furthermore, a good agreement between the results of ACA (measured by indirect immunofluorescence) and 21-OH autoantibodies (Abs) indicates that 21-OH Abs are the major component of the ACA (56)(57)(58)(59)(60).…”
Section: Adrenal Autoantigensmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to autoantibodies to CYP21A2, autoantibodies to two other steroidogenic enzymes, P450 side chain cleavage (CYP11A1) and 17a-hydroxylase (CYP17), which convert cholesterol to pregnenolone, and progesterone to 17-hydroxyprogesterone, respectively, are present. 21,[25][26][27] Since these latter enzymes, unlike CYP21A2, are expressed in the ovary, the presence of these antibodies may signify the actual autoimmune targets of the ovary. Antibodies targeting P450ssc and CYP17 are termed 'steroid cell' (SC) antibodies, since in addition to binding the adrenal cortex, they bind placental syncytiotrophoblast cells, Leydig cells of the testes, and theca and luteal cells of the ovary.…”
Section: Autoimmune Oophoritis As a Cause For Primary Ovarian Insuffimentioning
confidence: 99%
“…Furthermore, autoantibodies against CYP11A1, CYP21A2 and CYP17 are frequently found. 25 While APS-1 is rare globally, in several populations the frequency is increased (1 : 9000 in Iranian Jews; 1 : 14 000 in Sardinians; 1 : 25 000 in Finns). APS-1 was identified as a monogenic disease caused by function-disrupting mutations in the AutoImmuneREgulator gene (AIRE).…”
Section: Autoimmune Oophoritis As a Cause For Primary Ovarian Insuffimentioning
confidence: 99%